Profit Coordination and Optimization of Agricultural Product Brand Promotion Lead by Farmer Cooperative Organizations - Fangfang Guo; Ivan Ka Wai Lai; Tao Zhang; Yaoguang Zhong (Complexity)
In the e-commerce supply chain of agricultural products, there are three parties: farmer cooperative organizations, e-commerce platforms, and consumers. This study aims to investigate how to coordinate farmer cooperative organizations and e-commerce platforms to maximize the overall profits of the supply chains of agricultural products. Based on the Stackelberg game theory, this paper constructs a two-level supply chain decision-making model led by farmers’ cooperatives and followed by e-commerce platforms. It discusses two supply chain decision-making models (decentralized and centralized) with decision variables (selling price and promotion effort). The results show that the overall profit of the supply chain under centralized decision making is higher than the overall profit under decentralized decision making. In order to achieve the coordination of agricultural product sales price and brand promotion efforts and achieve win-win cooperation, this paper puts forward two coordination schemes: (1) coordinating revenue sharing, cost sharing, and wholesale price discounts and (2) coordinating the wholesale price. These two contract coordination schemes are verified by example analysis. Finally, the following strategies are recommended, including strengthening the investment in brand promotion and contract management.